Seed certification, certified seeds use and yield outcomes in Nigeria: Insights from nationally-representative farm panel data and seed company location data - Takeshima, Hiroyuki; Ragasa, Catherine; Bamiwuye, Temilolu; Andam, Kwaw S.; Spielman, David J.; Edeh, Hyacinth O.; Fasoranti, Adetunji; Haile, Beliyou; Nwagboso, Chibuzo; Omoigui, Lucky O.; Abdoulaye, Tahirou; Kumar, P. Lava; et al. (Elsevier, 2025)
CONTEXT Despite the importance of enhanced seed quality to agricultural productivity growth, evidence remains scarce regarding the nature and possible drivers of returns to formal sector quality assurance systems, including certified seeds production in countries like Nigeria that focus significantly on the formal-sector seed systems. OBJECTIVE This study narrows this knowledge gap by estimating the effect of the quantity of certified seeds produced and the spatial variations where they are produced on the use of certified seeds and yields. We also assess the yield effects of certified seeds use and their relationship with agroclimatic and socioeconomic conditions. METHODS We combine nationally-representative farm-household survey panel data with spatial data on the headquarters locations of seed companies, the quantity of certified seeds for maize, cowpea, and rice that they produce, and spatially explicit agroecological data. We apply panel fixed effects methods as well as instrumental-variable methods to address potential endogeneity associated with certified seeds use while also controlling for the use of improved varieties to separate their effects from the effects of certified seeds. RESULTS AND CONCLUSIONS Our findings indicate that the availability of certified seeds—captured by indicators of certified seeds produced by seed companies headquartered in the states of survey respondents—is associated with positive but declining marginal effects on certified seeds use and yields. These results are robust when we also consider the potential within-state heterogeneity in the proximity to seed company headquarters, as well as potential spillovers from the nearest adjacent states. The yield effects of certified seeds are heterogeneous and depend on agroclimatic conditions and farmers' socioeconomic characteristics. The use of certified seeds is somewhat higher in areas with higher yield effects after controlling for certified seeds production. These patterns partly lead to observed non-linearities in certified seeds use because certified seeds may be more likely to be used by farmers with higher expected returns than farmers with lower expected returns. These results underscore the importance of spatially targeted efforts in enhancing certified seeds production capacity, together with the exploration of intermediate quality standards in the short term where costs of seed certification are high relative to returns. SIGNIFICANCE The study provides unique quantitative evidence in a nationally representative framework in an African country that returns to seed certification systems in the current setting significantly vary depending on contexts, including agroclimatic conditions.